The chalk box kid - Bulla, Clyde Robert; Allen, Thomas B. (Thomas Burt), 1928-2004. (New York : Random House, 1987)
Nine-year-old Gregory's house does not have room for a garden, but he creates a surprising and very different garden in an unusual place.
G1
Keywords: Artists -- Fiction; Imagination -- Fiction; Gardens -- Fiction